2009
DOI: 10.1103/physrevb.79.214405
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for domain wall pinning and potential landscape modification by artificially patterned traps in ferromagnetic nanowires

Abstract: The interaction mechanism between transverse domain walls ͑TDWs͒ in Permalloy nanowires and artificially patterned traps is studied using high-sensitivity spatially resolved magneto-optical Kerr effect measurements and numerical simulations. T-shaped trap geometries are considered, where a DW traveling in the horizontal arm is pinned by the vertical arm. Pinning strengths as well as potential energy modifications created by the traps are measured, and the roles of the different DW characteristic parameters, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 30 publications
(25 reference statements)
1
39
0
3
Order By: Relevance
“…Figure 5d We now consider the pinning required to form energetically unfavourable monopoles. Domain-wall spectroscopy in permalloy nanowires demonstrated that remote magnetic charge provides effective domain-wall pinning 21 only out to 100 nm and revealed a local pinning potential well within the magnetic Coulomb barrier at an isolated permalloy Q = +1 T -vertex 22 . We conclude that local vertex effects dominate and the inset of Fig.…”
Section: (R Ijmentioning
confidence: 99%
“…Figure 5d We now consider the pinning required to form energetically unfavourable monopoles. Domain-wall spectroscopy in permalloy nanowires demonstrated that remote magnetic charge provides effective domain-wall pinning 21 only out to 100 nm and revealed a local pinning potential well within the magnetic Coulomb barrier at an isolated permalloy Q = +1 T -vertex 22 . We conclude that local vertex effects dominate and the inset of Fig.…”
Section: (R Ijmentioning
confidence: 99%
“…10͒ and a T-shaped trap. 11 The two possible equilibrium pinned configurations for a head-to-head DW are shown in Fig. 1͑a͒: the trap acts either as a potential well or a potential barrier, depending on the orientation of the magnetization in the core of the DW, and the two equilibrium configurations can be clearly distinguished by measuring the depinning field.…”
mentioning
confidence: 99%
“…distinguishing narrow-P from wide-AP or wide-P from narrow-AP); the clear difference in magnitude between the parallel and antiparallel switching fields means that different chiralities can reliably be distinguished. Note that micromagnetic simulations 18 showed that in the narrow-AP case, the DW incident on the trap splits into two DWs; the second DW moves along the vertical arm and switches it. In the wide-AP case, the "transmission field" does not correspond to transmission of the DW past the trap, but instead to re-nucleation of a new domain next to the trap.…”
Section: Effect Of Not Gates On Dw Chirality: Testing For Chiralmentioning
confidence: 99%
“…These measurements were already carried out in Ref. 18, but for nanostrips of different dimensions, which were fabricated using focused ion beam patterning rather than electron beam lithography. We therefore fabricated additional structures with a trap only (no NOT gate) and measured the transmission field for each different DW-trap configuration.…”
Section: Effect Of Not Gates On Dw Chirality: Testing For Chiralmentioning
confidence: 99%
See 1 more Smart Citation